Analisa Desain Konfigurasi dan Kapasitas Pada Sistem On – Grid Dengan Implementasi Pada PV Saat Waktu Beban Puncak Menggunakan HOMER - Anjar Rahmawati, Luluk; Dalimi, Rinaldy (ENERGI & KELISTRIKAN, 2024)
This research aims to provide information and methodology that functions to reduce electricity costs in the industrial sector which previously used fossil fuel as electricity fuel by using renewable energy using the Homer application. This research uses photovoltaics installed on the roof of an industry in Bekasi, Indonesia, as time management for industrial peak loads. So that obtain the lowest price with the best system, several scenarios are used that use comparisons to obtain the most appropriate and useful results for this industry. The first scenario is implemented only with the PLN power grid without photovoltaics, or PV. The second scenario applies PV installed and working during industrial WBP (peak load times) with BESS (Battery Energy Storage System), and the rest is carried out by the PLN electricity network with PV at industrial peak load times. The third is a scenario with PV and PLN electricity grid connection with low capital expenditure (material prices) but in compliance with needs. With the three types of scenarios above, a comparison of LCOE, NPV and IRR is used as a reference for the three scenarios and a third scenario is obtained that meets this industry. This is proven by economic results, namely, there is a decrease in daily tariffs to $0.0818/kWh, IRR 11%, NPV $14.6M and pay back period 8.6 years.